Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1098/rspb.2018.2867
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of ant larvae in the defence against social parasites

Abstract: Temporary social parasite ant queens initiate new colonies by entering colonies of host species, where they begin laying eggs. As the resident queen can be killed during this process, host colonies may lose their entire future reproductive output. Selection thus favours the evolution of defence mechanisms, before and after parasite intrusion. Most studies on social parasites focus on host worker discrimination of parasite queens and their offspring. However, ant larvae can also influence brood composition by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 76 publications
2
14
0
Order By: Relevance
“…One explanation for precise discrimination between nestmate and non-nestmate eggs in F. fusca is the potential threat of intraspecific parasitism, which occurs when a founding queen takes over an established conspecific colony and hijacks its workforce. Low relatedness among F. fusca nestmate queens (Hannonen et al 2004;Bargum et al 2007) and the fact that even larvae seem to discriminate between nestmate and nonnestmate eggs (Pulliainen et al 2019) support the idea that intraspecific parasitism shapes discrimination abilities in this species. Together, these results underline that phylogeny, ecology and within-colony social context are major factors mediating conspecific brood discrimination.…”
Section: Interactions With Conspecificsmentioning
confidence: 81%
See 2 more Smart Citations
“…One explanation for precise discrimination between nestmate and non-nestmate eggs in F. fusca is the potential threat of intraspecific parasitism, which occurs when a founding queen takes over an established conspecific colony and hijacks its workforce. Low relatedness among F. fusca nestmate queens (Hannonen et al 2004;Bargum et al 2007) and the fact that even larvae seem to discriminate between nestmate and nonnestmate eggs (Pulliainen et al 2019) support the idea that intraspecific parasitism shapes discrimination abilities in this species. Together, these results underline that phylogeny, ecology and within-colony social context are major factors mediating conspecific brood discrimination.…”
Section: Interactions With Conspecificsmentioning
confidence: 81%
“…Nevertheless, a study on egg signature mixtures in Formica ants showed that egg chemical profiles are highly variable and potentially provide sufficient information for discrimination between matrilines within nests (Helanterä and d'Ettorre 2014). Whether or not this information is used likely depends on species-specific biology: in contrast to F. exsecta, F. fusca is a common host to ant social parasites and displays excellent discrimination abilities (Helanterä and Sundström 2007;Helanterä and Ratnieks 2009a;Chernenko et al 2011Chernenko et al , 2013Helanterä et al 2011;Martin et al 2011;Pulliainen et al 2019). Contrasting patterns of brood discrimination in different species may thus be linked to differential selection pressures.…”
Section: Maternity and Kinshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps due to high parasite pressure, F. fusca workers and larvae exhibit precise discrimination abilities against con- and heterospecific individuals 20–25 , making it an ideal species to study the molecular correlates of communication. In addition, F. fusca larvae have been shown to consume both con- and heterospecific eggs 25,26 , showing that even larvae are able to discriminate friend from foe. This provides the unique opportunity to study how nutritional stimulation in the form of egg consumption affects developmental gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…Although our study design made it difficult to disentangle whether female-biased groups cooperated more simply because they had more females (that each contribute more) or whether males too increase their effort in the presence of many sisters, our results raise the possibility that D. pini larvae have some means to recognize their kin as well as the sex of the other individuals in the group, adjusting their cooperative behaviour accordingly. Potential mechanisms include CHP-compounds, already known to be important in nest-mate recognition both in immature and mature life-stages in eusocial ant species (28, 29). In this context, it is interesting to note that individuals were divided into the experimental groups as smaller instars, and differences in their defensive behaviour were consistent until the last larval instar.…”
Section: Discussionmentioning
confidence: 99%